Persistent chromosomal aberrations in somatic cells in testicular cancer patients after different therapies - Bilban-Jakopin, Cvetka (Radiology and oncology (Ljubljana), 2001)
Background. The damage due to radiation or chemotherapeutic agents has been estimated successfully for the last 35 years from the numbers of the chromosome changes. This finding may serve as biological dosimeter. The aim ofthe study was to find persistent chromosomal aberrations in somatic cells intesticular cancer patients after different therapies. Patients and methods. This prospective study includes 60 patients with testicular tumours. With respect to the histological results and various therapies that they were giventhey were divided into four groups. Prior to treatment, we did not detectany deviations either in the genome picture of our patients or in that of the subjects of the control group without malignant disease. The changes inthe genome of individual cells after therapy were detected by the following tests: structural chromosomal aberrations (SCA) test, sister chromatid exchange (SCE) test and micronucleus (MN) test performed on binuclear lymphocytes. (Abstract truncated at 2000 characters)
Keywords: Chromosome aberrations; kromosomi; Kromosomske aberacije; Micronucleus tests; Mikronukleus testi; rak (medicina); Sestrska kromatida, izmenjava; Sister chromatid exchange; somatske celice; Testicular neoplasms; Testis, novotvorbe; Therapy; zdravljenje